Hubungan antara status kesehatan balita dengan kejadian pneumonia di indonesia (analisis data riskesdas 2018) - Howay, Susan Yulia Laura; Sutarto, Sutarto; Larasati, TA; Nareswari, Shinta (CV. Jasa Sukses Abadi, 2026)
Pneumonia is a leading cause of under-five mortality in Indonesia. Several risk factors—such as low birth weight, incomplete immunization, lack of exclusive breastfeeding, and poor nutritional status—contribute to the high mortality rate. This study aims to determine the prevalence of pneumonia and the distribution of low birth weight, immunization status, nutritional status, and exclusive breastfeeding among Indonesian children under five, as well as to analyze their associations with pneumonia. This study used secondary data from the 2018 National Basic Health Research (Riskesdas) covering 34 provinces in Indonesia with a cross-sectional design. Samples were selected using probability proportional to size (PPS) with a two-stage sampling method. Data were analyzed using the chi-square test. The results of statistical tests in this study showed that there was a significant relationship between birth weight status and nutritional status with the incidence of pneumonia (p value = 0.000; 95% CI, 1.269-1.996; OR = 1.592) and (p value = 0.029; 95 % CI, 1.023-1.449; OR = 1.218), while the results of statistical tests also showed that there was no significant relationship between immunization status and exclusive breastfeeding status with the incidence of pneumonia (p value = 0.656; 95% CI, 0.808-1.137; OR = 0.958 ) and (p value = 0.803; 95% CI, 0.832-1.153; OR = 0.979). In the conclusion, a significant association was found between birth weight status and nutritional status with the occurrence of pneumonia.